A review on techniques for improving power quality: research gaps and emerging trends - Vasupalli Manoj; Prabodh Khampariya; Ramana Pilla (Bulletin of Electrical Engineering and Informatics, 2022)
Many issues have arisen for the electricity sector because of the widespread use of gadgets that rely on electrical power. India's energy demands are rising rapidly due to the country's rapid economic development. These days, almost every industry makes extensive use of electrical machinery and equipment. Electronic gadgets add a non-linear demand to the power grid, which can cause power quality (PQ) problems such as voltage fluctuations that can damage electrical equipment and even knock the grid down. As the use of DG units becomes more commonplace, complications related to power conversion interfaces, load switching, and other factors emerge as potential bottlenecks in service. Power filters were first created several decades ago to address problems with PQ and to dampen harmonics caused by nonlinear loads. This document summarises previous studies that have investigated the effectiveness of power filters and other techniques for enhancing power quality. There are also descriptions of research that is still going on and where it stands, as well as a look ahead to what its possible future benefits might be.